Comparable COVID‐19 outcomes with current use of GLP‐1 receptor agonists, DPP‐4 inhibitors or SGLT‐2 inhibitors among patients with diabetes who tested positive for SARS‐CoV‐2. Issue 6 (16th February 2021) - Israelsen, Simone Bastrup; Pottegård, Anton; Sandholdt, Håkon; Madsbad, Sten; Thomsen, Reimar Wernich; Benfield, Thomas
Abstract: Incretin‐based therapies, glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) and dipeptidyl peptidase‐4 inhibitors (DPP‐4i), have been hypothesized to exert beneficial effects on COVID‐19 outcomes due to anti‐inflammatory properties. In this population‐based cohort study, we retrieved data from nationwide registries on all individuals diagnosed with severe acute respiratory syndrome coronavirus 2 infection up to 1 November 2020. For individuals with diabetes, we examined the impact of use of GLP‐1 RAs (n = 370) and DPP‐4i (n = 284) compared with sodium‐glucose cotransporter‐2 inhibitors (SGLT‐2i) (n = 342) on risk of hospital admission and severe outcomes. Relative risks (RRs) were calculated after applying propensity score weighted methods to control for confounding. Current users of GLP‐1 RAs had an adjusted RR of 0.89 (95% confidence interval 0.34‐2.33), while users of DPP‐4i had an adjusted RR of 2.42 (95% confidence interval 0.99‐5.89) for 30‐day mortality compared with SGLT‐2i use. Further, use of GLP‐1 RAs or DPP‐4i compared with SGLT‐2i was not associated with decreased risk of hospital admission. Thus, use of incretin‐based therapies in individuals with diabetes and severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) was not associated with improved clinical outcomes.